Pemberdayaan Aktif Pelaku UMK dalam Menggapai Keunggulan Bersaing Berbasis Inovasi Produk dan Media Sosial - Nurhidayati Nurhidayati; Satria Sukmawan (Jurnal Riptek, 2023)
The aim of this research is to find out, analyze and test the influence of product innovation and social media, both partially together, on the competitive advantage of MSEs in Tembalang District, Semarang City, as well as to find out, analyze and test the influence of product innovation and social media both together. on the competitive advantage of MSEs in Tembalang District, Semarang City. Data collection was carried out by survey using a questionnaire given to 47 SMEs in Tembalang Village, Semarang City. The analysis tool used is the SPSS '26 program. The results of the research show that product innovation partially has a positive and significant effect on the competitive advantage of MSEs in Tembalang Village, Semarang City, social media partially has a positive and significant effect on the competitive advantage of MSEs in Tembalang Village, Semarang City, while jointly product innovation and social media have a positive and significant influence on the competitive advantage of MSEs in Tembalang Village, Semarang City.